Art, Politics, and Interdisciplinary Collaboration: A Conversation with Jeff Lieberman. - Davis, Jacquelyn (Afterimage)
An interview with American interdisciplinary artist Jeff Lieberman is presented. He discusses his various degrees and career progression, including his studies in physics, mechanical engineering, and robotics. He reminisces his first interests in primary and secondary school like Lego. He talks about his first projects like "Dani Eyes," and "The Drip Project [273-o73A]."